Fraud and Understanding the Moral Mind: Need for Implementation of Organizational Characteristics into Behavioral Ethics - Houdek, Petr (Science and engineering ethics, 2020)
The development of behavioral ethics has brought forth a detailed understanding of the processes of moral perception, decision-making and behavior within and beyond organizations and communities. However, prescriptive recommendations of behavioral research regarding how to support an ethical environment often underestimate the specifics of organizational characteristics that may encourage the occurrence and persistence of dishonesty, especially regarding deception as a desired action in some instances by some employees and managers. Furthermore, behavioral research does not adequately recognize the notion that dishonesty can be sometimes viewed as an acceptable cost for some expected traits or skills of an employee such as intelligence or creativity. Under some conditions, deception can be even considered a moral, prosocial activity. Finally, formal ethics systems and situational measures to promote honesty may be inefficient or directly harmful. This article highlights questions of how to assess such factors in research on (un)ethical behavior within organizations.
Keywords: Creativity; etika; podvádění; Morals; Fraud; podvod; Selection; Organizational trade-offs; kreativita; lidé; Dishonesty; Organizational culture; Deception; Humans; Ethics; mravy; Behavioral ethics